To the question about the therapeutic tactics in patients with cerebral supratentorial stroke - L.O. Shevchenko; V. I. Bobrova; V. M. Kalashnik (Zaporozhye State Medical University, 2013)
The vascular diseases of brain grew considerably in the economic developed countries, what stipulates the actuality of this problem. Consequences of supratentorial cerebral strokes are motor deficits, violations of speech and psychic-pathological syndromes, which initiate the search of new medical methods and more argued therapeutic tactics in patients with this pathology. Hypoperfusion of the brain, consequence stipulating the development of pathological cascade, that increases structural changes of brain in the postinsult patients, and initiates the pathological systems, which cause to development of neglect-syndroms, have negative effects on the course of postinsult neurological syndromes. AIM OF ARTICLE: The investigation of postinsult syndromes, also neglect syndromes in the brain as the result of the reaction on the sharp brain's damage (stroke), that initiates inhibition of neurorehabilitation, and also the substantiation of therapeutic tactics for this pathology. The facts, which contend negative impact on the process of neurorehabilitation, are confirmed and testify that the pathological systems (according to the conception of G.Kryzhanovsky) may initiate the origin of neglect-syndromes and are capable to inhibit neurorehabilitation in postinsult patients. Postinsult neurological syndromes must be contended through the proper scales. The scale of NIHSS, D.W. Barthel Scale, Rankin Scale and other are used in clinical practice. There is also presence of motor-neglect integrating with other postinsult syndromes in postinsult patients with neglect-syndromes, that initiates difficulty of neurological violations therapy. THE MATERIALS AND METHODS Motor-neglect is characterized by the extrapyramidal dysfunctions, psychic-pathological syndromes and cognitive violations, and is incurable or therapy of neurological pathology has weak effects. So neglect-syndromes render the negative effect on rehabilitation process. Information of EEG-pattern in postinsult patients exposed the disorganization of bioelectric activity of brain with motor-neglect, that is showed by the presence of delta-activity in central, temporal and frontal leads. The literary information confirms that neglect-syndromes, motor-neglect are associated with the lesion of basal neuroganglions, mesolobus, structures of hippocampus and other medio-basal formations. DEDUCTIONS: 1. The therapeutic measures for patients with postinsult motor deficiency with motor-neglect should be differentiated and also must ensure the inhibition of negative effects on the processes of neurorehabilitation. 2. The problem of postinsult syndromes and neglect-syndromes are actual and expedient in theoretical and clinical aspects